2002
DOI: 10.14411/eje.2002.040
|View full text |Cite
|
Sign up to set email alerts
|

The assemblages of aquatic Coleoptera from shallow lakes in the northern Iberian Meseta: Influence of environmental variables

Abstract: Abstract. Aquatic Coleoptera in shallow lakes associated with the Canal de Castilla (Palencia Province, Spain) in the northern Ibe rian Meseta were sampled over the course of a year (spring 1998-winter 1999). These waterbodies are typical plateau wetlands with dense vegetation and vary in permanence and area (from 3.3 ha to 29.35 ha). Oxygen concentration, conductivity and pH were recorded at the time of sampling. Lake area, depth, water permanence and type of vegetation were also taken into account. Ninety tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 24 publications
3
18
0
5
Order By: Relevance
“…This is explained by the combination of these factors, which formed a gradient from the interior (temporal wetlands at high altitude with low values of conductivity) to the coast (permanent wetlands at low altitude with high values of conductivity) in our study area. This result is in agreement with other studies that found a relationship between these factors and changes in the composition of aquatic beetle assemblages (Valladares et al, 1990(Valladares et al, , 2002Eyre et al, 1992;Garrido et al, 1994;Fairchild et al, 2003). However, in the study of Picazo et al (2012) altitude, conductivity and anthropogenic impact were the most important factors, but hydroperiod did not seem to be a key factor in assemblage composition.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is explained by the combination of these factors, which formed a gradient from the interior (temporal wetlands at high altitude with low values of conductivity) to the coast (permanent wetlands at low altitude with high values of conductivity) in our study area. This result is in agreement with other studies that found a relationship between these factors and changes in the composition of aquatic beetle assemblages (Valladares et al, 1990(Valladares et al, , 2002Eyre et al, 1992;Garrido et al, 1994;Fairchild et al, 2003). However, in the study of Picazo et al (2012) altitude, conductivity and anthropogenic impact were the most important factors, but hydroperiod did not seem to be a key factor in assemblage composition.…”
Section: Discussionsupporting
confidence: 92%
“…Conductivity is a good indicator of different types of pollution, like waste waters, mining or fertilizers (de Paz, 1993;García-Criado, 1999;Trigal, 2006), but in the case of the group 3 it can be considered a natural stressor due to the influence of saline water in coastal lagoons. The species that most contributed in this group was Ochthebius viridis fallaciosus, exclusively collected in coastal lagoons and typical of habitats with high values of conductivity or salinity (Valladares et al, 2002;Garrido and Munilla, 2008). Other species typical of coastal lagoons that contributed to the group characterization was Limnebius furcatus, which was only captured in this type of habitat, confirming the results of other studies for this species in Galicia (Díaz- Pazos and Otero, 1993;Garrido and Sáinz-Cantero, 2004;Garrido and Munilla, 2008).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Such perennial plants, when they also cover a broad area (owing to an extended root system), exhibit high richness, abundance and diversity of Coleoptera (Scheffer, 1998;Thomaz and Cunha, 2010). In the lakes under study, Salvinia formed a dense vegetation cover, which favored the high taxon richness observed among the Coleoptera, also observed by Valladares et al (2002) in shallow lakes located at one end of the Castille Canal, north of the Meseta Ibérica. Fontanarrosa et al (2013) also reported a dominance of those coleopterans associated with macrophytes, in two lakes in the province of Buenos Aires, Argentina.…”
Section: Discussionmentioning
confidence: 82%